The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1373/clinchem.2012.191957
|View full text |Cite
|
Sign up to set email alerts
|

External Quality Assessment of Point-of-Care Methods: Model For Combined Assessment of Method Bias and Single-Participant Performance by the Use of Native Patient Samples and Noncommutable Control Materials

Abstract: BACKGROUND: An important objective in external quality assessment (EQA) is to evaluate systematic deviations between methods. However, this is not possible when noncommutable control materials are used. The aim of this study was to develop an EQA model that incorporates a method bias evaluation using native patient samples into EQA schemes in which noncommutable materials are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…65 A further consideration for POC testing success is the implementation of appropriate quality control measures. Participation in external quality control programs or proficiency testing (EQA, external quality assessment) 66,67 is a possibility and can assist in monitoring quality of results. It is critical to follow the manufacturer's instructions in the use of external quality control materials for regular quality control surveillance.…”
Section: Poc Analytical Accuracy and Performance: Room For Improvementmentioning
confidence: 99%
“…65 A further consideration for POC testing success is the implementation of appropriate quality control measures. Participation in external quality control programs or proficiency testing (EQA, external quality assessment) 66,67 is a possibility and can assist in monitoring quality of results. It is critical to follow the manufacturer's instructions in the use of external quality control materials for regular quality control surveillance.…”
Section: Poc Analytical Accuracy and Performance: Room For Improvementmentioning
confidence: 99%
“…First, external quality assurance programs often rely on noncommutable material with unknown matrix effects that blind participants from knowing whether their devices operate with bias. By adding knowledge about bias from prospective commutability studies at several facilities, Stavelin et al showed that more complete external quality assurance for POC testing could be achieved (26 ). DETECT enables calculation of this bias through use of the EMR and could be orchestrated by external quality assurance programs at minimal costs.…”
Section: Discussionmentioning
confidence: 99%
“…However, by these processes macromolecules are denatured and the matrix of materials is changed during the preparation [12,13]. The problems are especially severe for the EQA and PT organisers due to the need for large volumes of stable materials in small tubes to be distributed to all participating laboratories in each survey [14]. It is difficult to obtain such large volumes of fresh genuine human materials; so the organisers rely on outdated human materials, which are often supplemented with animal constituents or synthetic components [15].…”
Section: Introductionmentioning
confidence: 99%